China’s poverty alleviation over the last 40 years: successes and challenges - Liu, Mingyue; Feng, Xiaolong; Wang, Sangui; Qiu, Huanguang (The Australian journal of agricultural and resource economics, 2020)
Over the past 40 years, China has made significant progress towards its poverty alleviation goals. The rural population under the current poverty line has decreased by 739.9 million. China has contributed to more than 70 per cent of world poverty reduction. To better promote the new anti‐poverty strategy and to serve as a reference for poverty alleviation in other developing countries, this paper summarises the main experiences of China’s poverty alleviation over the past 40 years and then discusses the challenges associated with implementing the targeted poverty alleviation policy in the new era. China’s experience with poverty alleviation includes development‐oriented poverty alleviation, improving self‐development capabilities of the poor population, encouraging multiple subjects to participate in poverty alleviation and focusing on innovation and ways to improve poverty alleviation. Although China’s poverty alleviation initiatives have achieved significant successes, there are still several challenges that should be of concern in the coming years, such as the diminishing marginal effect of financial inputs on poverty alleviation, the resulting negative incentives for the poor to improve their internal motivations and the insufficient participation of markets and social forces in poverty alleviation. Given these challenges, this paper provides suggestions for anti‐poverty policies beyond 2020.